Assessing the potential of using Virtual Reality based approaches for enhancing the professional development of teachers - Stavroulia, Kalliopi Evangelia (Department of Multimedia and Graphic Arts, Faculty of Fine and Applied Arts, Cyprus University of Technology, 2020)
This research proposes the use of an innovative Virtual Reality (VR) based framework in teacher practical training methodology, offering a new paradigm in teacher education. This research addresses modern needs for the use of technology-based approaches in teaching and learning, aiming to promote the professional development of teachers. The development of the VR tool followed a multiphase research design consisting of five phases. Additionally, the target audience was actively involved during the entire research process providing significant feedback to the researcher that resulted in the development of a high-quality VR training tool that meets real teachers' needs and challenges and has a strong added value. Multiple instruments were used to measure the effectiveness of the VR training tool including the use of Electroencephalography (EEG) devices, wristband hand monitors, questionnaires, interviews, and focus groups. The research outcomes indicated the potential of using VR in teacher training. The outcomes revealed a strong impact of the VR intervention on participants’ emotions and the potential on the cultivation of empathy skills. Moreover, the results are statistically significant related to other parameters under investigation, including the sense of presence and perspective-taking.
Keywords: Virtual reality; Teacher education; Teacher training; Empathy; Emotions